One move but two movements: an alternative account of the middle construction - Dai, Hui; Wang, Heyu (Frontiers in Language Sciences, 2025)
The A-movement analysis of the middle construction leaves the oblique middles untouched and fails to explain the unique syntactic and semantic properties of middle clauses. Under the assumption that the tense-defective Mod (Modal) INFL heads the middle structure, we advocate a combination of A-movement and A'-movement analysis of the middle construction. Specifically, we propose that the seemingly patient/adjunct subject of a middle clause is the external argument of cause licensed by the causative verb. Also, the relevant NP-movement from spec-vP to spec-ModP (specifier of the Modal Phrase) is one move but two movements in that C might DONATE both [TOP] feature and phi-features to the tense-defective Mod. This analysis provides a package account for the syntax and semantics of middle clauses and theoretically proves the existence of a universal syntactic entity of the middle construction. Our study incorporates various Chinese middle sentences into the universal grammar framework and verifies that the middle construction is a cross-language universal syntactic entity, adding evidence to its psychological reality.